CONFLICT LOGICAL COMPETENCE OF THE MANAGER AS A COMPONENT OF HIS PERSONAL EFFECTIVENESS - Сазонова, Тетяна; Курченко, Антон; Солодчук, Тарас (SWorldJournal, 2023)
The work examines the concept and meaning of the manager's conflict-related competence, its importance for the formation of the manager's personal effectiveness system. Recommendations for the formation of an effective conflict management system are give